Appreciate time and life well being - Nur Sa’adatul Afzan, Jusoh (2020)
The global Covid-19 outbreak has affected the world entire population in general and in Pahang specifically, some students still stay on the campus of Universiti Malaysia Pahang (UMP) in Gambang and Pekan due to the Movement Control Order (MCO) directive.